2020
DOI: 10.1007/s13197-020-04414-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of high- and low-molecular-weight glutenin subunits from Chinese Xinjiang wheat landraces and historical varieties

Abstract: Landraces and historical varieties are necessary germplasms for genetic improvement of modern cereals. Allelic variations at the Glu-1 and Glu-3 loci in 300 common wheat landraces and 43 historical varieties from Xinjiang, China, were evaluated by Sodium-dodecyl-sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and allele-specific molecular markers. Among the materials investigated, three, nine, and seven alleles were identified from the Glu-A1, Glu-B1, and Glu-D1 loci, respectively, and a total of 26 high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
5
8
0
Order By: Relevance
“…In the current study, the frequency of the Glu-D1a (2+12) allele was far higher in the landraces than commercial cultivars. Previous reports also showed that the allele Glu-D1a (2+12) was the most frequent in Chinese and Japanese wheat landraces (Dai et al 2020, Nakamura 2000, Zhang et al 2002, Zheng et al 2011. For commercial cultivars, allele Glu-D1a (2+12) also appeared more than allele Glu-D1d (5+10) although the latter allele also appeared as a common allele, which is in agreement with previous results (Gao et al 2018, Liu et al 2005.…”
Section: Bs Breeding Sciencesupporting
confidence: 88%
“…In the current study, the frequency of the Glu-D1a (2+12) allele was far higher in the landraces than commercial cultivars. Previous reports also showed that the allele Glu-D1a (2+12) was the most frequent in Chinese and Japanese wheat landraces (Dai et al 2020, Nakamura 2000, Zhang et al 2002, Zheng et al 2011. For commercial cultivars, allele Glu-D1a (2+12) also appeared more than allele Glu-D1d (5+10) although the latter allele also appeared as a common allele, which is in agreement with previous results (Gao et al 2018, Liu et al 2005.…”
Section: Bs Breeding Sciencesupporting
confidence: 88%
“…López-Fernández et al (2021) the Glu-B1 locus in the 189 Spanish landraces analysed, among which the allele i coding for HMW-GS 17+18 was found at a low frequency of 1.59%. The same tendency for this allele was described by Dai et al (2020) who found it in only spring forms of Chinese Xinjiang wheat landraces and historical cultivars.…”
Section: Resultssupporting
confidence: 81%
“…Some rare combinations (i.e., 5+12, 2+12*, 12, and 2+10´) appeared at a low frequency. These combinations have been previously described in other germplasm collections [ 62 , 63 , 64 ], but this is the first time that they have been reported in Iberian landraces, probably due to the large number of and high diversity in the accessions analyzed here.…”
Section: Discussionsupporting
confidence: 56%
“…This may be due to the difficult assignment of this glutenin subunit using only standard SDS-PAGE electrophoresis but could also indicate that it is characteristic of Iberian landraces [42]. Regarding the Glu-B1 locus, it is worth noting that Spanish landraces present a high frequency of the subunit pairs 20x+20y and 13+16, whereas these combinations are absent in landraces from other regions of the world [60][61][62][63][64], indicating the specific conservation of these alleles in the Iberian Peninsula. The 13+16 pair has also been described at a high frequency (88%) in Triticum aestivum ssp.…”
Section: Discussionmentioning
confidence: 99%